Chemical and electrochemical properties of a hydrophobic deep eutectic solvent. (1st February 2019) - Ruggeri, S.; Poletti, F.; Zanardi, C.; Pigani, L.; Zanfrognini, B.; Corsi, E.; Dossi, N.; Salomäki, M.; Kivelä, H.; Lukkari, J.; Terzi, F.
Abstract: Hydrophobic deep eutectic solvents (DESs) have been recently introduced and acknowledged to offer remarkable advantages over the common organic solvents, thanks to their biodegradability, low toxicity and low cost. In the present paper a first study of the electrochemical properties and extraction capabilities of a prototypical hydrophobic DES, based on tetrabutylammonium chloride-decanoic acid (1:2 M ratio), is carried out. A small water content is shown to be advantageous as it dramatically affects the electrical conductivity and viscosity of the solvent, i.e. the parameters of fundamental importance in electrochemistry. A critical environmental pollutant, namely Cr(VI), has been successfully extracted from aqueous phase and amperometrically detected in the DES phase.